Identification of random resource shares in collective households without preference similarity restrictions - Geoffrey R. Dunbar; Arthur Lewbel; Krishna Pendakur (Bank of Canada, 2017)
Resource shares, defined as the fraction of total household spending going to each person in a household, are important for assessing individual material well-being, inequality and poverty. They are difficult to identify because consumption is measured typically at the household level, and many goods are jointly consumed, so that individual-level consumption in multi-person households is not directly observed. We consider random resource shares, which vary across observationally identical households. We provide theorems that identify the distribution of random resource shares across households, including children's shares. We also provide a new method of identifying the level of fixed or random resource shares that does not require previously needed preference similarity restrictions or marriage market assumptions. Our results can be applied to data with or without price variation. We apply our results to households in Malawi, estimating the distributions of child and female poverty across households.
Keywords: D13; D11; D12; C31; I32; 330; Domestic demand and components; Econometric and statistical methods